CURA ENGGANG: PENCIPTAAN TARI DARI GERAK BURUNG ENGGANG BETINA - Siti Rahmadani Nur Bakhtiar; Nurlina Syahrir (xxxx, 2022)
Tari Cura Enggang mengangkat tema Fauna yang menggambarkan peniruan gerak dari Burung Enggang. Terciptaanya karya ini bertujuan mendeskripsikan proses kerja tahap awal penciptaan karya tari Cura Enggang dan merealisasikan gerak dari burung enggang betina serta mengkresikan tari terbaru yang berkiblat pada gerak tradisi untuk diolah dalam tercapai penataan gerak tari Cura Enggang. Proses penciptaan Proses kerja tahap awal penciptaan karya tari Cura Enggang dideskripsikan melalui pematangan ide, pematangan tema, pematangan judul, pematangan tipe tari, pematangan alur atau struktur dramatik, pematangan model penyajian, pematangan dan penetapan penari. Realisasi gerak dari Burung Enggang betina dan mengkreasikan tari terbaru yang berkiblat pada gerak tradisi tari enggang untuk diolah dalam tercapai penataan gerak  tari Cura Enggang. Mengeskplorasi diri mencari bentuk bentuk. Burung Enggang  betina yang indah serta pengembangan dari gerak tari Burung Enggang sehingga menghasilkan tari  kreasi terbaru yaitu Cura Enggang. Realisasi proses penciptaan karya tari Cura Enggang melalui: proses eksplorasi, improvisasi, forming, penata dengan penari, penata dengan busana dan rias, penata dengan pemusik, penata dengan lighting, penata property dan pertunjukan. Kata Kunci: Cura Enggang, Gerak, Burung Enggang Betina AbstractThe Cura Enggang dance raises the Fauna theme which describes the imitation of the motion of the hornbill. The creation of this work aims to describe the work process in the early stages of creating the Cura Enggang dance work and realizing the movements of the female hornbill and creating the latest dance that is oriented to traditional movements to be processed in achieving the arrangement of the Cura Enggang dance movements. The process of creation The work process in the early stages of creating a Cura Enggang dance is described through maturation of ideas, maturation of themes, maturation of titles, maturation of dance types, maturation of dramatic plots or structures, maturation of presentation models, maturation and determination of dancers. Realization of the movements of the female hornbills and creating the latest dances that are oriented to the traditional hornbills dance movements to be processed in achieving the arrangement of the Cura hornbills dance movements. Explore yourself looking for shapes. The beautiful female hornbill and the development of the hornbill dance movement have resulted in the newest dance creation, Cura hornbill. The realization of the process of creating Cura Enggang dance works through: exploration, improvisation, forming, stylists with dancers, stylists with clothes and make-up, stylists with musicians, stylists with lighting, property and performance stylists. Keywords: Cura Enggang, Motion, Female Hornbill